DECISION-MAKING VISUALISATION APPUCATION BASED ON ARGUMENT-AS METAPHOR - John Edan, Shirlene Meredith (Universiti teknologi petronas, 2008)
This document will examine the need of visualisation in assisting in decision making in the financial world. Observation is comprehension. This principle is central to all visualisation. Here, the necessary for visualisation is explained and the process involved in this project. People have difficulty making optimal decisions about their financial future, this is due to investment decisions are very difficult because they involve money and can impact our quality oflife. This project will focus on the research paper about Argument-as Metaphor in Decision- Making Visualisation. As an innovative alternative way in understanding the financial data, this report describes by using application developed based on the research paper may assist decision-maker specifically, the investors, in decision-making on their respective investment.